Anaphylaxis to mango fruit - Forkel, Susann; Cevik, Naciye; Heetfeld, Anne; Hipler, Uta-Christina; Buhl, Timo (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Mangifera indica (commonly known as mango) is a species of the flowering plant which bears juicy stone-fruits (drupes) and belongs to the family of Anacardiaceae. The most prominent countries for the cultivation and production of mango fruits are India and China. During recent years, mango fruit has enjoyed increasing popularity in Western Europe and elsewhere. Anaphylaxis induced by mango ingestion has been rarely reported [1–5]. Besides anaphylaxis, also delayed hypersensitivity reactions to mango have been reported anecdotally [2].